An intelligent bioreactor system for the cultivation of a bioartificial vascular graft. Issue 5 (28th December 2016) - Maschhoff, Paul; Heene, Sebastian; Lavrentieva, Antonina; Hentrop, Thorleif; Leibold, Christian; Wahalla, Marc‐Nils; Stanislawski, Nils; Blume, Holger; Scheper, Thomas; Blume, Cornelia
Abstract : Cardiovascular disease is the most common cause of death, accounting for 31% of deaths worldwide. As purely synthetic grafts implicate concomitant anticoagulation and autologous veins are rare, tissue‐engineered vascular grafts are urgently needed. For successful in vitro cultivation of a bioartificial vascular graft, the suitable bioreactor should provide conditions comparable to vasculogenesis in the body. Such a system has been developed and characterized under continuous and pulsatile flow, and a variety of sensors has been integrated into the bioreactor to control parameters such as temperature, pressure up to 500 mbar, glucose up to 4.5 g/L, lactate, oxygen up to 150 mbar, and flow rate. Wireless data transfer (using the ZigBee specification based on the IEEE 802.15.4 standard) and multiple corresponding sensor signal processing platforms have been implemented as well. Ultrasound is used for touchless monitoring of the growing vascular structure as a quality control before implantation (maximally achieved ultrasound resolution 65 μm at 15 MHz). To withstand the harsh conditions of steam sterilization (120°C for 20 min), all electronics were encapsulated. With such a comprehensive physiologically conditioning, sensing, and imaging bioreactor system, all the requirements for a successful cultivation of vascular grafts are available now.